Validation of simplified Indian Diabetes Risk Score for screening undiagnosed diabetes in an urban setting of Haryana. (December 2017) - Rajput, Meena; Garg, Dinesh; Rajput, Rajesh
Abstract: Background and objectives: Identification of at risk individuals using simple screening tools like Indian Diabetes Risk Score (IDRS) and appropriate life style interventions could greatly help in preventing or delaying the onset of diabetes and thus reducing the burden of disease. Material and method: 450 individuals >20 years who consented to participate were selected randomly from three anganwadis of urban area of Rohtak city. Demographic characteristics and anthropometric measurements such as weight, height and waist circumference were taken. BMI was calculated. IDRS developed by Mohan et al. was applied for categorizing the individuals as high risk, moderate risk and low risk. World Health Organization (WHO) criterion of fasting blood glucose ≥126 mg/dl was used for diagnosing diabetes. Results: 54% of individuals were categorized as high risk followed by 37.6% as moderate risk as per IDRS risk score. Prevalence of diabetes was more in ≥50 years age group (28.6%) as compared to 35–49 years (14.2%) and 20–35 years age group (6.0%). Individuals with no physical activity had significantly high prevalence of diabetes as compared to mild or moderate physical activity (P 0.004). Similarly, males with waist circumference ≥100 cm and females with ≥90 cm had significantly high prevalence of diabetes (P 0.000 and P 0.005). On multiple logistic regression analysis age, family history of diabetes and BMI were independent predictors of diabetes. Conclusion: Diabetes is a rising epidemic. Early screening and appropriate interventions at the start are needed for control of disease and risk factor modifications.